Practical Approach to Mixed Methods Research for Clinicians - Chandrasekharan, Nishida (Nepal Journal of Epidemiology, 2019)
As a clinician, finding the time as well as the opportunity to pursue and follow research actively is usually quite challenging. Moreover, with the passage of time, a focus on developing research falls by the wayside in our emphasis on patient care and the related demands on time and energy.